Dynamics of Digital Transformation in Human Resource Training at Depo Khing Guan Jember - Alifian Nugraha; Sampir Andrean Sukoco; Aryu Ramadhani Hiedayat (ABM: International Journal of Administration, Business and Management, 2025)
This study explores the dynamics of digital transformation in human resource training at Depo Khing Guan Jember, a regional logistics center undergoing operational modernization. As organizations shift from traditional to technology-based systems, employee training becomes a strategic tool for ensuring adaptability and performance. This research adopts a qualitative descriptive approach, utilizing interviews, field observations, and documentation to investigate how digital training is implemented and experienced within the depot. The study focuses on educational processes, systematic procedures, technical skill development, knowledge-based learning, and the prioritization of hands-on practice. Findings reveal that digital platforms, such as Learning Management Systems (LMS) and interactive simulations, are effectively used to enhance employee competencies and operational efficiency. The research highlights the importance of structured, practice-oriented training in supporting digital readiness among employees. Additionally, the study identifies organizational challenges and opportunities in aligning training programs with technological advancements. These insights contribute to a deeper understanding of digital transformation strategies within mid-sized logistics operations and offer practical implications for human resource development in similar contexts.